The development of lectora inspires media in learning mathematics fractions material - Asih Mardati; Lina Annisa; Yeyen Febrilia; Desfa Yusmaliana (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
This research aims to consider pointed to decide the steps in creating Lectora Inspire learning media and its possibility for arithmetic learning of divisions for third-grade basic school understudies. The investigation was investigation and improvement. The advancement forms concerned the improvement show proposed by Thiagarajan's 4D. The 4D development model included the stages of (1) Define, (2) Design, (3) Development, and (4) Dissemination. The information collection rebellious utilized were master appraisal sheets, instructor evaluation sheets, and understudy appraisal sheets. The result about appeared that Lectora inspire media gotten a rate of 77.3% within the